The antibacterial activity and mechanism of imidazole chloride ionic liquids on Staphylococcus aureus - Hu, Yanhui; Xing, Yuyuan; Ye, Peng; Yu, Haikuan; Meng, Xianglei; Song, Yuting; Wang, Gongying; Diao, Yanyan (Frontiers in Microbiology, 2023)
Ionic liquids (ILs) have garnered increasing attention in the biomedical field due to their unique properties. Although significant research has been conducted in recent years, there is still a lack of understanding of the potential applications of ILs in the biomedical field and the underlying principles. To identify the antibacterial activity and mechanism of ILs on bacteria, we evaluated the antimicrobial potency of imidazole chloride ILs (CnMIMCl) on Staphylococcus aureus (S. aureus). The toxicity of ILs was positively correlated to the length of the imidazolidinyl side chain. We selected C12MIMCl to study the mechanism of S. aureus. Through the simultaneous change in the internal and external parts of S. aureus, C12MIMCl caused the death of the bacteria. The production of large amounts of reactive oxygen species (ROS) within the internal parts stimulated oxidative stress, inhibited bacterial metabolism, and led to bacterial death. The external cell membrane could be destroyed, causing the cytoplasm to flow out and the whole cell to be fragmented. The antibacterial effect of C12MIMCl on skin abscesses was further verified in vivo in mice.